Focus on: INSIDE / OUTSIDE - Stehlíková Babyrádová, Hana; Horáček, Radek; Kamenický, Petr; Nedomová, Jana; Ovčáčková, Jana (Masaryk University Press, 2019)
Title in English: Focus on: INSIDE / OUTSIDE Focus on: INSIDE / OUTSIDE catalog reflects the activities of the Department of Art Education of the Faculty of Education at Masaryk University in the last ten years. The text points out the pedagogical and publishing activities of teachers, creative and gallery activities and, last but not least, innovative projects connected with the arts.